2016
DOI: 10.1007/s00705-016-2756-4
|View full text |Cite
|
Sign up to set email alerts
|

The fecal virome of South and Central American children with diarrhea includes small circular DNA viral genomes of unknown origin

Abstract: Viral metagenomics of feces collected from 58 Peruvian children with unexplained diarrhea revealed several small circular ssDNA genomes. Two genomes related to sequences previously reported in feces from chimpanzees and other mammals and recently named smacoviruses were characterized and then detected by PCR in 1.7 % (1/58) and 19 % (11/58) of diarrheal samples, respectively. Another three genomes from a distinct small circular ssDNA viral group provisionally called pecoviruses encoded Cap and Rep proteins wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Smacoviruses [15,17], previously also referred to as chipoviruses [22,24], have been identified in faecal matter of various vertebrates, including humans, as well as in the abdomina of dragonflies of two species (Table 1). Thus far, none of these viruses have been cultured or found in animal tissue sample.…”
mentioning
confidence: 99%
“…Smacoviruses [15,17], previously also referred to as chipoviruses [22,24], have been identified in faecal matter of various vertebrates, including humans, as well as in the abdomina of dragonflies of two species (Table 1). Thus far, none of these viruses have been cultured or found in animal tissue sample.…”
mentioning
confidence: 99%
“…Human disease-related viruses, which can cause diarrhea, respiratory diseases, conjunctivitis, meningoencephalitis, and infantile gastroenteritis (Fong et al, 2010;Nguyen et al, 2007) were also identified. Some of these that might cause gastroenteritis, such as human picobirnavirus and human feces pecovirus (Giordano et al, 1999;Phan et al, 2016;Phan et al, 2012), were widely detected in the sewage samples but are usually not tested for at hospital laboratories. To understand their importance for public health, more enteric viruses identified in environmental samples should be incorporated into the routine monitoring of patients with gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…1). While the tropism of some CRESS DNA viruses, such as circoviruses (infecting vertebrates) and geminivirus (infecting plants), has been clearly defined, the large majority of such genomes have been characterized using metagenomics from environmental or nonsterile samples, such as feces (13,24,26,35,(62)(63)(64)(65). The tropism of the large majority of CRESS DNA viruses is therefore still unknown (66).…”
Section: Discussionmentioning
confidence: 99%